The Influence of Quality of Work Life and Islamic Work Ethics Towards Job Performance among SMEs’ Employee - Wahibur Rokhman; Forbis Ahamed (Ekonomi Syariah IAIN Kudus, 2021)
This study aims to scrutinize the contribution of quality of work life and Islamic work ethics to the job performance of employees who work for Small and Medium Enterprises (SMEs) in Central Java, Indonesia. A deductive questionnaire survey approach was applied to make sure data gathering reaches out across business sectors particularly, most of the registered SMEs throughout central Java. About 354 valid responses were analyzed utilizing SPSS in order to be able to examine how much quality work life of employees in the light of ethical values practice in Islam impact the performance of employees. The outcomes of the study revealed a tremendous effect on the performance of employees in SMEs while their work lives are taken cared for by the company. Similarly, performance found to be overwhelmingly determined by work ethics reflexively applied in a densely populated peninsula of Javanese Muslims. This is reconfirmed when IWE predisposed a significant positive relationship with quality of work life. The results of this study, as expected, provide theoretical and practical gains to the body of knowledge as well as become an impetus for all the likewise faith base business communities across the region, particularly for SMEs’ owner/manager and certainly for future researchers.